Pengembangan Spin Game Berbasis Power Point Sebagai Media Evaluasi Mata Pelajaran Praktikum Akuntansi Lembaga - Alfi Hariati Puspitasari; Rochmawati Rochmawati (Jurnal Studi Guru dan Pembelajaran, 2022)
This study aims to develop a powerpoint-based spin game as a medium for evaluating institutional accounting practicum subjects for class XI accounting. Research and Development (R&D) was conducted to determine the feasibility of the product developed using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The subjects of this study were students of class XI Accounting at SMK Negeri 6 Surabaya. Data were obtained from interviews, observations, and questionnaires in the form of material expert validation questionnaires, media experts and student responses. The results of the assessment with material validation obtained a percentage of 91.6% in the "very feasible" category, media expert validation obtained a percentage of 80% in the "enough" category, while student responses obtained a percentage of 89% in the "enough category".The assessment states that the power point-based spin game evaluation media is appropriate for use in institutional accounting practicum subjects for class XI accounting.